E-CRM features in the context of airline e-ticket purchasing: a conceptual framework - Ismail, Nor Alina; Hussin, Husnayati (2013)
During the past ten years the impact of the internet on channel selection has been dramatic and pervasive throughout the business world. Yet strong arguments can be made that few industries have been as invasively affected as has the airlines industry. Currently travelers increasingly choose the websites to search for flight ticket or other things. This paper discusses a proposed conceptual model for the e-ticketing online transaction cycle especially in “pre-purchase, purchase and post-purchase”. The main focus of the model is to examine the effect of e-CRM features on customer satisfaction and customer loyalty in the context of e-ticketing transaction.